An integrated study of geochemistry and mineralogy of the Upper Tukau Formation, Borneo Island (East Malaysia): Sediment provenance, depositional setting and tectonic implications. (1st August 2017) - Nagarajan, Ramasamy; Roy, Priyadarsi D.; Kessler, Franz L.; Jong, John; Dayong, Vivian; Jonathan, M.P.
Graphical abstract: Highlights: Integrated approach to infer weathering, provenance and tectonic setting of the Tukau Formation. High maturity and moderate to intensively weathered sedimentary rocks. The Schwaner Mountains and Tin Belt of the Malaysia Peninsular were principal provenances. Minor contribution from the mafic and ultramafic rocks. Deposition in a passive margin with passive collisional and rift settings. Abstract: An integrated study using bulk chemical composition, mineralogy and mineral chemistry of sedimentary rocks from the Tukau Formation of Borneo Island (Sarawak, Malaysia) is presented in order to understand the depositional and tectonic settings during the Neogene. Sedimentary rocks are chemically classified as shale, wacke, arkose, litharenite and quartz arenite and consist of quartz, illite, feldspar, rutile and anatase, zircon, tourmaline, chromite and monazite. All of them are highly matured and were derived from a moderate to intensively weathered source. Bulk and mineral chemistries suggest that these rocks were recycled from sedimentary to metasedimentary source regions with some input from granitoids and mafic-ultramafic rocks. The chondrite normalized REE signature indicates the presence of felsic rocks in the source region. Zircon geochronology shows that the samples were of Cretaceous and Triassic age. Comparable ages of zircon from the Tukau Formation sedimentary rocks, granitoids of the Schwaner Mountains (southern Borneo) and Tin Belt of the Malaysia Peninsular suggest that the principal provenance for the Rajang Group were further uplifted and eroded during the Neogene. Additionally, presence of chromian spinels and their chemistry indicate a minor influence of mafic and ultramafic rocks present in the Rajang Group. From a tectonic standpoint, the Tukau Formation sedimentary rocks were deposited in a passive margin with passive collisional and rift settings. Our key geochemical observation on tectonic setting is comparable to the regional geological setting of northwestern Borneo as described in the literature.